Oxygen isotopic composition of ice of the glacier № 30, Suntar-Khayata Mountains - N. A. Budantseva; B. R. Mavlyudov; Ju. N. Chizhova; Yu. K. Vasil’chuk (Лëд и снег)
The object of research is the mountain-valley glacier № 30, located in the central part of the Suntar-Khayatа Ridge – one of the largest centers of modern glaciation of the North-East of Russia. This glacier had been chosen due to lamination of ice on its surface, providing successive sampling of increasingly young ice upward the glacier slope. At the end of August 2013, surface ice of the glacier was sampled within the altitude range 2060–2510, an age of this ice here was estimated to be about 500 years old. Variations of δ18О values in the glacier ice amounted about 5.5‰: from −20.2 to −25.9‰ that is numerically consistent with isotopic values for the neighboring glaciers № 29 and 31. No essential relation between the ice isotopic composition and altitude, age or the change of the ice granularity was found. Absence of high-altitude isotope effect is explained by the fact that preciptation on the glacier № 30 falls at the same level of condensation as well as by intensive infiltration-congelation ice formation and fixation in the firn and snow cover of a part of the meltwater coming from higher and steeper areas on gently sloping sites of the glacier. The δ18О values of ice from glacier № 30 are rather «heavy» for glaciers being formed in severe climate conditions with average January temperature of −28 °C. According to Dansgaard's dependence δ18Оprecipitation – t °Cair the winter snow on the glacier № 30 should be hypothetically characterized by the δ18О values from −30 to −40‰ which are typical ones for the winter snow in Siberia. Oxygen isotope values of the ice show insignificant contribution of winter snow into formation of the glacier and prevalence of spring-autumn snowfalls. No definite trend of changes in the glacier alimentation and the ice-formation process was found for the last 500 years.